2012
DOI: 10.1007/s13205-012-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture condition for enhanced decolorization and degradation of azo dye reactive violet 1 with concomitant production of ligninolytic enzymes by Ganoderma cupreum AG-1

Abstract: The strain Ganoderma cupreum AG-1 (Genbank accession no. HQ328947) isolated from the decayed wood was evaluated for its ability to decolorize azo dye reactive violet 1 as well as for the production of ligninolytic enzymes. In the initial decolorization study, the strain was capable of decolorizing 19 different azo dyes. The strain was capable of decolorizing dye over a pH range of 4.5–6 at 30 °C. The optimum pH was found to be 4.5. Various other process parameters like additional carbon and nitrogen source and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 29 publications
(31 reference statements)
2
8
0
1
Order By: Relevance
“…. The spectral setup observed was found similar to that reported in other photodegradation reports (Gahlout et al, 2013;Neoh et al, 2015). recombination sites have to be reduced by synthesizing a photocatalysts with better crystallinity (Ângelo et al, 2013).…”
Section: Evaluation Of Extent Of Photodegradation Of Rb5 Dyesupporting
confidence: 81%
“…. The spectral setup observed was found similar to that reported in other photodegradation reports (Gahlout et al, 2013;Neoh et al, 2015). recombination sites have to be reduced by synthesizing a photocatalysts with better crystallinity (Ângelo et al, 2013).…”
Section: Evaluation Of Extent Of Photodegradation Of Rb5 Dyesupporting
confidence: 81%
“…The peak at 2354.62 cm -1 corresponds to the stretching vibrations of cyclic bonds. Peaks at 1657.53 cm -1 and 1383.60 cm -1 assigned to carbonyl stretching vibrations as reported by [44]. The peak at 1534.10 cm -1 showed -N=O stretching vibrations [45].…”
Section: Ftir Analysissupporting
confidence: 56%
“…In addition, some studies have reported the presence of carbon and nitrogen sources acting as co-substrates, favoring decolorization and stimulating enzyme production (Levin et al 2010, Andrade et al 2013, Gahlout et al 2013. Hou et al (2004), reported laccase production associated with low nitrogen concentration in culture.…”
Section: Introductionmentioning
confidence: 99%